Antimicrobial resistance: A global emerging threat to public health systems. Issue 13 (2nd September 2017) - Ferri, Maurizio; Ranucci, Elena; Romagnoli, Paola; Giaccone, Valerio
ABSTRACT: Antimicrobial resistance (AMR) became in the last two decades a global threat to public health systems in the world. Since the antibiotic era, with the discovery of the first antibiotics that provided consistent health benefits to human medicine, the misuse and abuse of antimicrobials in veterinary and human medicine have accelerated the growing worldwide phenomenon of AMR. This article presents an extensive overview of the epidemiology of AMR, with a focus on the link between food producing-animals and humans and on the legal framework and policies currently implemented at the EU level and globally. The ways of responding to the AMR challenges foresee an array of measures that include: designing more effective preventive measures at farm level to reduce the use of antimicrobials; development of novel antimicrobials; strengthening of AMR surveillance system in animal and human populations; better knowledge of the ecology of resistant bacteria and resistant genes; increased awareness of stakeholders on the prudent use of antibiotics in animal productions and clinical arena; and the public health and environmental consequences of AMR. Based on the global nature of AMR and considering that bacterial resistance does not recognize barriers and can spread to people and the environment, the article ends with specific recommendations structured around a holistic approach and targeted to different stakeholders.